Pemberian Reward dalam Meningkatkan Motivasi Belajar Siswa di Madrasah Ibtidaiyah - Muhammad Hafiz (PT. Global Pustaka Ilmiah, 2025)
This study aims to analyze the effect of rewards on students’ learning motivation and achievement in Islamic elementary schools based on a review of various scholarly sources. Rewards serve as positive reinforcement that enhances students’ enthusiasm, self-confidence, and discipline during the learning process. The review shows that appropriate and proportional rewards can strengthen intrinsic motivation, especially when aligned with the principles of fairness, sincerity, and Islamic educational values. Educational rewards not only improve academic performance but also foster positive character traits such as responsibility and perseverance. However, excessive or misapplied rewards may reduce students’ genuine motivation to learn. Therefore, teachers should balance material and non-material rewards and integrate them with Islamic values to ensure that rewards are both educational and sustainable.